STRATEGI PENGEMBANGAN MEDIA DAKWAH BERBASIS PENDIDIKAN KESEHATAN - Evalinda Evalinda; Siti Nuri Nurhaidah; Nurfitria Farhana; Hayatuddin Hayatuddin; Khairul Hidayat; Agus Idwar Jumhadi; Nabiel Al Musawa (Al-Idaroh: Media Pemikiran Manajemen Dakwah, 2025)
This research focuses on developing health-based da'wah as a holistic approach to increasing public health awareness within the framework of Islamic values. Health-based da'wah integrates religious teachings with modern health principles to encourage sustainable behavior change. In Islam, maintaining health is seen as a spiritual responsibility, as explained in the Koran and hadith, such as the importance of cleanliness, healthy eating patterns, and maintaining physical, mental and spiritual balance. The research method uses a qualitative-descriptive approach by examining Islamic literature and public health practices. This research found that da'wah bil hal, namely da'wah through concrete actions, is an effective method for conveying Islamic values ​​that are relevant to health. Examples include educating the public about the importance of maintaining cleanliness through the teaching "cleanliness is part of faith" or promoting healthy eating patterns by referring to the recommendations of the Prophet Muhammad. The research results show that health-based da'wah is able to reach various levels of society, both in urban and rural areas. This approach is also relevant for addressing increasing mental health challenges, especially in urban communities. In addition, collaboration between religious leaders, health practitioners and government institutions is needed to expand the impact of this da'wah. The research conclusion confirms that health-based da'wah not only plays a role in improving people's physical and mental well-being, but also strengthens spiritual awareness as a basis for living a healthy lifestyle according to Islamic teachings.